Respuesta :

Answer:

6 - 4a

Step-by-step explanation:

From the question given,

f(x) = 2 - x

2f(a) + f(2a) =.?

First, we shall obtain f(a). This can be obtained as follow:

f(x) = 2 - x

x = a

f(a) = 2 - a

Next, we shall obtain 2f(a). This is can be obtained as follow:

f(a) = 2 - a

2f(a) = 2(2 - a)

2f(a) = 4 - 2a

Next, we shall obtain f(2a). This can be obtained as follow:

f(x) = 2 - x

x = 2a

f(2a) = 2 - 2a

Finally, we shall determine 2f(a) + f(2a) as follow:

2f(a) = 4 - 2a

f(2a) = 2 - 2a

2f(a) + f(2a) =?

2f(a) + f(2a) = (4 - 2a) + (2 - 2a)

2f(a) + f(2a) = 4 - 2a + 2 - 2a

2f(a) + f(2a) = 4 + 2 - 2a - 2a

2f(a) + f(2a) = 6 - 4a

Therefore, 2f(a) + f(2a) is equivalent to 6 - 4a